A hybrid approach to complex bilateral common iliac artery and internal iliac artery aneurysm repair - Jeremy Obrand, MSc; Melissa Jones, MSc, MD; Anirudh Mirakhur, MD, FRCPC, DABR; Kenton Rommens, MD, FRCSC; Randy Moore, MD, FRCSC, FACS (Journal of Vascular Surgery Cases and Innovative Techniques, 2024)
A case of a young patient with incidental bilateral internal iliac artery aneurysms and common iliac artery aneurysms is described. A staged hybrid surgical approach was performed to preserve pelvic perfusion, with bilateral stent grafts deployed into an ipsilateral anterior division branch and contralateral posterior division branch of the internal iliac arteries. One week later, an open infrarenal aorto-bi-iliac graft was performed with distal anastomoses to the previously deployed stent grafts. The findings from the present case add to the growing number of reported cases of hybrid repair of bilateral internal iliac and common iliac artery aneurysms with preservation of pelvic perfusion.